STroke imAging pRevention and Treatment (START): A Longitudinal Stroke Cohort Study: Clinical Trials Protocol. Issue 4 (June 2015) - Carey, Leeanne M.; Crewther, Sheila; Salvado, Olivier; Lindén, Thomas; Connelly, Alan; Wilson, William; Howells, David W.; Churilov, Leonid; Ma, Henry; Tse, Tamara; Rose, Stephen; Palmer, Susan; et al.
Rationale: Stroke and poststroke depression are common and have a profound and ongoing impact on an individual's quality of life. However, reliable biological correlates of poststroke depression and functional outcome have not been well established in humans. Aims: Our aim is to identify biological factors, molecular and imaging, associated with poststroke depression and recovery that may be used to guide more targeted interventions. Design: In a longitudinal cohort study of 200 stroke survivors, the START – STroke imAging pRevention and Treatment cohort, we will examine the relationship between gene expression, regulator proteins, depression, and functional outcome. Stroke survivors will be investigated at baseline, 24 h, three-days, three-months, and 12 months poststroke for blood-based biological associates and at days 3–7, three-months, and 12 months for depression and functional outcomes. A sub-group ( n = 100), the PrePARE: Prediction and Prevention to Achieve optimal Recovery Endpoints after stroke cohort, will also be investigated for functional and structural changes in putative depression-related brain networks and for additional cognition and activity participation outcomes. Stroke severity, diet, and lifestyle factors that may influence depression will be monitored. The impact of depression on stroke outcomes and participation in previous life activities will be quantified. Study Outcomes: Clinical significance lies in the identification of biological factors associated with functional outcome to guide prevention and inform personalized and targeted treatments. Evidence of associations between depression, gene expression and regulator proteins, functional and structural brain changes, lifestyle and functional outcome will provide new insights for mechanism-based models of poststroke depression.